Kepatuhan Diet dan Minum Obat pada Pasien Gagal Jantung yang Mengalami Rehospitalisasi - Widyasari, Ni Luh Wiwik; Puspawati, Ni Luh Putu Dewi; Azis, Abdul; Muliawati, Ni Kadek (STIKes YARSI Pontianak, 2025)
Background: Heart failure is a complex clinical condition associated with a high risk of rehospitalization and increased mortality. Rehospitalization is often influenced by patients' adherence to dietary recommendations and medication regimens. Objective: This study aimed to identify the levels of dietary and medication adherence among heart failure patients who experienced rehospitalization. Method: A quantitative descriptive study with a retrospective approach was conducted at the Integrated Cardiac Care Unit of Prof. Dr. I.G.N.G Ngoerah General Hospital in Denpasar, Bali. Data were collected using the DSR-SCB Scale and the MARS-10 questionnaire. A total of 86 participants were selected using purposive sampling. Result: The result revealed that 64 patients (74.4%) demonstrated non-adherence to dietary recommendations, while only 22 patients (25.6%) were adherent. Regarding medication adherence, 50 patients (58.1%) were categorized as non-adherent, and 36 patients (41.9%) as adherent. Conclusion: Most patients who experience rehospitalization demonstrate non-adherence to both dietary recommendations and prescribed medications. Patient non-adherence may be associated with sociodemographic factors such as age, gender, and educational level, in addition to limited health literacy and inadequate family support. Reducing the risk of rehospitalization requires the implementation of structured discharge planning and the provision of comprehensive education for both patients and caregivers